(3GdCMcGe GdehVhYjI hGdELQGFjI ddLQGFe GdGfJNGHjI (B/ s - (3gfO YHO Gddg fGUQ Ydj GdSGOIs; (3YeQ eMeO eMeO SGde s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 2014)
(3ehVhY gPg GdOQGSI Mhd GdCMcGe GdehVhYjI hGdELQGFjI ddLQGFe GdGfJNGHjI, hJQLY CSHGH GNJjGQ GdehVhY Edi MOGKJg hCgejJg aj GdBhfI GdCNjQI, NGUI aj Xd GdCMOGK GdSjGSjI GdJj TgOJgG eYXe GdOhd efP ChGNQ GdYGe (B2010(3, hGdJj cGf ef Hjf CSHGHgG YOe fRGgI GdGfJNGHGJ aj Jdc GdOhd haQV ofXe oMce GSJHOGOjI, hcPdc JSdjW GdVhA Ydi GdJLGQH GdGfJNGHjI GdJj eQJ HgG HYV GdOhd, heG CSaQJ YfgG ef LQGFe; HSHH GfYOGe GdhYj GdSjGSj dOi GdeLJeY hYOe OQGjJg heYQaJg HYhGbH eKd gPg GdLQGFe, aVdkG Yf YOe JaYjd GdCMcGe GdNGUI HGdYbhHGJ GdebQQI Ydi GdCaYGd GdJj JeS GdGfJNGHGJ, MjK JYJeO GdOQGSI Ydi GdebGQfI aj gPG GdeLGd Hjf eNJda GdOhd hOhf MUQ, hHNGUI GdOhd GdJj oJYJHQ GdCcKQ NhVkG ddGfJNGHGJ hPdc dOQGSI GdeSJNdU ef JLGQHgG GdGfJNGHjI, heG CSaQ Yfg ef GfJgGcGJ(B.s
(3CWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFj (B2014.s
(3HHdjhLQGajG(B: (3UaMGJ (B167-170.s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdELQGAGJ GdJMVjQjI ddYedjI GdGfJNGHjIs; (3GdYedjI GdGfJNGHjIs; (3GdCMcGe GdehVhYjI s; (3LQjeI GdJQTjMs; (3GdJQTjM GdeJYOOs; (3GdOYGjI GdGfJNGHjIs; (3eQMdI GdJUhjJs; (3YedjI GdJUhjJs; (3dLfI GdGfJNGHGJs; (3GdJUhjJ HZjQ Mbs; (3MQjI GdJUhjJs; (3GddLGf GdGfJNGHjIs; (3GdQThI GdGfJNGHjIs; (3UfGOjb GdGbJQGYs; (3eQMdI GdaQRs; (3JSdje eMGVQ GdaQRs; (3GdeLJeY GdeOfjs; (3GdETQGa Ydi GdYedjI GdGfJNGHjIs; (3GdeQGbHI GdOhdjI hGdeMdjIs; (3GdgjFI GdbVGFjI GdeTQags; (3GdVHW aj GdLQGFe GdGfJNGHjIs; (3GdVHW GdEOGQj hGdVHW GdbVGFjs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs